Wound Care Using 0.9% NaCl and Aloe Vera on Bacterial Colony Count in Diabetic Rat Wounds - Rahayu, Sri Mulyati; Vitniawati, Vina; Suprapti, Tuti (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Inappropriate care of acute diabetic wounds increases the risk of infection. Proper wound dressing plays a crucial role in protecting wounds from microbial contamination. The principle of moist wound care is to keep the wound environment adequately hydrated. The combination of 0.9% NaCl and Aloe vera in wound care helps maintain wound moisture, while the antiseptic properties of Aloe vera inhibit bacterial growth. This study aimed to determine the effectiveness of wound care using 0.9% NaCl and Aloe vera. An experimental research method was used, involving eight rats with acute diabetic wounds. After wound induction, wound smears were taken and cultured for 24 hours to count bacterial colonies. Wound treatment was carried out for seven days using a combination of 0.9% NaCl and Aloe vera, applied every morning and evening. After the treatment period, bacterial colony counts were measured again. The results showed a significant difference in bacterial colony counts before and after treatment, with a p-value of 0.012 (< 0.05). It can be concluded that wound care using 0.9% NaCl and Aloe vera is effective in reducing bacterial colony counts.